Kinetics and Mechanism of the Gold‐Catalyzed Hydroamination of 1, 1‐Dimethylallene with N‐Methylaniline. Issue 40 (4th June 2021) - Harris, Robert J.; Nakafuku, Kohki; Duncan, Alethea N.; Carden, Robert G.; Timmerman, Jacob C.; Widenhoefer, Ross A.
Abstract: The mechanism of the intermolecular hydroamination of 3‐methylbuta‐1, 2‐diene (1 ) with N ‐methylaniline (2 ) catalyzed by (IPr)AuOTf has been studied by employing a combination of kinetic analysis, deuterium labelling studies, and in situ spectral analysis of catalytically active mixtures. The results of these and additional experiments are consistent with a mechanism for hydroamination involving reversible, endergonic displacement of N ‐methylaniline from [(IPr)Au(NHMePh)] + (4 ) by allene to form the cationic gold π‐ C1, C2 ‐allene complex [(IPr)Au(η 2 ‐H2 C=C=CMe2 )] + (I ), which is in rapid, endergonic equilibrium with the regioisomeric π‐ C2, C3 ‐allene complex [(IPr)Au(η 2 ‐Me2 C=C=CH2 )] + (I′ ). Rapid and reversible outer‐sphere addition of 2 to the terminal allene carbon atom of I′ to form gold vinyl complex (IPr)Au[C(=CH2 )CMe2 NMePh] (II ) is superimposed on the slower addition of 2 to the terminal allene carbon atom of I to form gold vinyl complex (IPr)Au[C(=CMe2 )CH2 NMePh] (III ). Selective protodeauration of III releases N ‐methyl‐ N ‐(3‐methylbut‐2‐en‐1‐yl)aniline (3 a ) with regeneration of 4 . At high conversion, gold vinyl complex II is competitively trapped by an (IPr)Au + fragment to form the cationic bis(gold) vinyl complex {[(IPr)Au]2 [C(=CH2 )CMe2 NMePh]} + (6 ). Abstract : Kinetic and spectroscopic analyses of the gold‐catalyzed hydroamination of 1, 1‐dimethylallene with N ‐methylaniline support a mechanism involving rapid and reversible addition of N ‐methylaniline to the more substituted terminus of gold π‐allene complex I to form gold vinyl complex II superimposed on slower addition of N ‐methylaniline to the less substituted terminus of I to form gold vinyl complex III . Selective formation of the linear allylic amine 3 a is attributed to the more facile protodeauration of III relative to II .